Evaluation of Costimulatory Molecules in Peripheral Blood Lymphocytes of Canine Patients with Histiocytic Sarcoma - Tagawa, Michihito (PLoS One, 2016)
Histiocytic sarcoma is a rapidly progressive and fatal neoplastic disease in dogs. It is unclear whether costimulatory molecules, including CD28, cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4), and programmed death-1 (PD-1), are expressed on peripheral blood lymphocytes (PBLs) of canine patients with histiocytic sarcoma. The objective of this study was to evaluate the expression of CD28, CTLA-4, and PD-1 molecules on PBLs of patients with histiocytic sarcoma, patients with other tumors, and healthy controls. Twenty-six dogs were included in the study, with eight, ten, and eight dogs in the histiocytic sarcoma, other tumor, and healthy control groups, respectively. PBLs and serum were prospectively obtained from patients diagnosed histopathologically with histiocytic sarcoma, other tumors and healthy controls. The surface expression of CTLA-4, CD28, and PD-1 on T lymphocytes was examined using flow cytometric analysis. Serum samples were frozen at −30°C until serum interferon-γ (IFN-γ) was measured by enzyme-linked immunosorbent assay. The expression level of CTLA-4 on CD4+ lymphocytes was significantly higher in the histiocytic sarcoma group than in the control group. The expression of CTLA-4 on CD8+ lymphocytes was significantly higher in the histiocytic sarcoma group than in the other two groups. In addition, the expression of PD-1 on CD8+ lymphocytes was significantly higher in the histiocytic sarcoma group than in the control group. However, no significant differences in CD28 expressions and serum IFN-γ levels were observed. The present results provided evidence showing that the expression levels of CTLA-4 on both CD4+ and CD8+ lymphocytes and PD-1 on CD8+ lymphocytes in peripheral blood obtained from dogs with histiocytic sarcoma were upregulated. The overexpressions of CTLA 4 and PD-1 suggested that antitumor immunity may be suppressed in dogs with histiocytic sarcoma.